Advancements in Radiology and Diagnostic Imaging - Łoginoff, Jan; Augustynowicz, Kinga; Świąder, Kinga; Ostaszewska, Sandra; Morawski, Przemysław; Pactwa, Filip; Popińska, Zuzanna (Journal of Education, Health and Sport, 2023)
Radiology and diagnostic imaging have undergone remarkable advancements in recent years, shaping the future of healthcare and improving patient outcomes. This review article provides an extensive overview of the developments and opportunities in various aspects of radiology, including CT, MRI, ultrasound, digital radiology, teleradiology, 3D printing, radiomics, radiogenomics, and nuclear radiology. It highlights the integration of artificial intelligence and machine learning in radiology, the emergence of theranostics, and the exploration of the human microbiome. The article also delves into advanced imaging techniques for cardiovascular diseases, hybrid imaging modalities in oncology, and optical imaging. The summary emphasizes the importance of continued innovation and development in radiology and diagnostic imaging to enhance patient care and global health outcomes.